Intrinsic determinants of prion protein neurotoxicity in Drosophila: from sequence to (dys)function - Cembran, Alessandro; Fernandez-Funez, Pedro (Frontiers in Molecular Neuroscience, 2023)
Prion diseases are fatal brain disorders characterized by deposition of insoluble isoforms of the prion protein (PrP). The normal and pathogenic structures of PrP are relatively well known after decades of studies. Yet our current understanding of the intrinsic determinants regulating PrP misfolding are largely missing. A 3D subdomain of PrP comprising the β2-α2 loop and helix 3 contains high sequence and structural variability among animals and has been proposed as a key domain regulating PrP misfolding. We leveraged the use of transgenic flies to identify the residues responsible for PrP toxicity. We combined in vivo work in Drosophila with molecular dynamics (MD) simulations, which provide additional insight to assess the impact of candidate substitutions in PrP from conformational dynamics. MD simulations revealed that in human PrP WT the β2-α2 loop explores multiple β-turn conformations, whereas the Y225A (rabbit PrPlike) substitution strongly favors a 310-turn conformation, a short right-handed helix. This shift in conformational diversity correlates with lower neurotoxicity in flies. We have identified additional conformational features and candidate amino acids regulating the high toxicity of human PrP and propose a new strategy for testing candidate modifiers first in MD simulations followed by functional experiments in flies. In this review we expand on these new results to provide additional insight into the structural and functional biology of PrP through the prism of the conformational dynamics of a 3D domain in the Cterminus. We propose that the conformational dynamics of this domain is a sensitive measure of the propensity of PrP to misfold and cause toxicity. This provides renewed opportunities to identify the intrinsic determinants of PrP misfolding through the contribution of key amino acids to different conformational states by MD simulations followed by experimental validation in transgenic flies.